"Between hope and hopelessness" : A qualitative exploration of 'born free' constructions of transformation in post-apartheid higher education - Liccardo, Sabrina Jr (University of Pretoria, 2022)
Dissertation (MA (Psychology))--University of Pretoria, 2021.